PENGARUH RELATIONSHIP QUALITY, BRAND EXPERIENCE DAN DESAIN PRODUK DENGAN MINAT BELI SEBAGAI VARIABEL INTERVENING TERHADAP KEPUTUSAN PEMBELIAN PRODUK PERALATAN RUMAH TANGGA - Nurlaila Hidayaty; Ginta Ginting; Kurniawati Kurniawati (STKIP Persada Khatulistiwa Sintang, 2022)
This study aims to analyze the influence of relationship quality, brand experience, and product design on purchasing decisions by mediating buying interests. Data was collected from 398 respondents who are Tupperware Indonesia members in seven major cities and had joined as a member for at least 1 year to fill out 38 questionnaire items tested for validity and reliability with confirmatory factor analysis (CFA). PT Tupperware Indonesia is a multinational company and a market leader in the plastic home appliance industry with an 18.5% market share in 2019. The data collection technique in this study used purposive sampling, and data analysis was carried out using the Structural Equation Model (SEM) AMOS 22 method. The results showed a positive and significant influence on relationship quality, brand experience, product design, and buying interest in purchasing decisions. And there is a positive and significant relationship between quality, brand experience, and product design influence buying decisions mediated by buying interest. The results of this study provide managerial implications for how to drive consumer purchasing decisions through improved relationship quality, providing an unforgettable brand experience and an understanding of product design that has aesthetic, functional, and symbolic value and a deeper understanding of the marketing of the home appliance industry